Development and validation of an instrument to identify the leader’s essential characteristics in knowledge sharing - de Oliveira Archanjo de Souza, Daniele Santos [UNESP]; Onias, Tamara; Marins, Fernando Augusto Silva [UNESP]; Faria Neto, Antônio [UNESP] (Taylor & Francis, 2024)
This article presents a development and validation process of questionnaires prepared by cross-referencing the characteristics required for leaders in Knowledge Sharing in the automotive industry. A survey was chosen considering the identification of validated questions about constructs, even if isolated, contained in the different instruments present in database publications. After 100% of the consulted specialists validated the questionnaires, they were pre-tested on a sample of 11 operators. With consistent statistical analysis, the results showed a Cronbach’s alpha above 0.7 for all questions and their relationship with each of the competencies. A relevant contribution of this work is to allow for the identification of the ideal leadership profile by indicating the necessary competencies, besides filling a gap in scientific literature once a search did not find specific instruments that relate themes nor studies exploring the application in the sample at hand.
Keywords: Knowledge management; Knowledge sharing; Leader characteristics; Leadership; Research instruments